Differential suppression of hippocampal network oscillations by neuropeptide Y - Pollali, Evangelia; Draguhn, Andreas (Neuropharmacology, 2024)
Neuropeptide Y (NPY) is the most abundant neuropeptide in the brain. It exerts anxiolytic and anticonvulsive actions, reduces stress and suppresses fear memory. While its effects at the behavioral and cellular levels have been well studied, much less is known about the modulation of physiological activity patterns at the network level. We therefore studied the impact of NPY on two prominent, memory-related hippocampal activity patterns, gamma oscillations and sharp wave-ripple complexes in C57BL/6 male mice. Using established in vitro brain slice models for both patterns, we assessed the effects of NPY and receptor-specific agonists and antagonists on network activity in the CA3 and CA1 subnetworks. We report that NPY strongly suppresses sharp waves, and has significant, but much weaker effects on the power of carbachol-induced gamma oscillations. Both effects are primarily mediated via Y2 receptors. Additionally, NPY effects are much more prominent in the CA1 region compared to CA3. Our results show pattern- and region-specific effects of NPY on hippocampal networks, which suggest specific modulatory actions on hippocampus-dependent memory processes.
Gesehen am 10.07.2025